Coordination mechanism of SaaS service supply chain: Based on compensation contracts - Yanli Guo; Jianbin Chen; Hailing Guo; Xinman Lu (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this paper is to build new contracts theories of SaaS service supply chain. Software as a Service (SaaS) has become a hot topic in this industry . Compared with traditional manufacturing supply chain and general service supply chain, the new IT service supply chain which based on SaaS has characteristics of both service and IT. And SaaS is completely different from traditional software package model. Therefore the classic contracts, which be widely used in traditional manufacturing supply chain, can't be directly applied in SaaS service supply chain. The necessary way of IT services developing is to study the SaaS service supply chain combining with characteristics of SaaS. Therefore, It focuses on the coordination of SaaS service supply chain. Design/methodology/approach: It tries to answer the following question: how do the ISV motivate SaaS operators to improve the service level through effective contracts mechanism under conditions of asymmetric information. In order to answer these questions, this paper does some researches including: Under the conditions of information asymmetry, supposing the service level (is related to the degree of effort) of SaaS operator was private information, we construct model of compensation contract, i.e., to motivate SaaS operator to improve service level through transfer payments of compensation price. Findings and Originality/value: The study finds out that when ISV get to "positive feedback", instead of the traditional market equilibrium, compensation contract (linear) can coordinate satisfactorily the SaaS service supply chain. In the point of "positive feedback", the marginal revenue equals the marginal cost, but it is not the equilibrium of ISV'profit-maximization. Research limitations/implications: There are some limitations in this research. In the linear compensation contracts, the compensation price is fixed value. If in the contract, we can create a change value which is related to the sales volume of service, the coordination efficiency of compensation will be increased. And in the future, the nonlinear compensation contracts should be researched.Practical implications: In the practical implication, it will promote the development of study and practice of SaaS and IT service industry. And it is beneficial to ISV, platform operators and customers. Originality/value: From the theoretical perspective, this paper put forward some new contracts and motivating mechanism for effective coordination of SaaS service supply chain and the conclusion will enrich content of service supply chain theory system. In theory, it has more significance for further researching on SaaS and service supply chain.
Keywords: 650; SaaS (Software as a Service); service supply chain; compensation contracts; coordination; the service level; positive feedback